Tissue Engineering: Current Technology for Facial Reconstruction - Fenberg, Rachel; vonWindheim, Natalia; Malara, Megan; Ahmed, Maariyah; Cowen, Erin; Melaragno, Luigi; Vankoevering, Kyle (Facial Plastic Surgery, 2023)
Facial reconstruction is a complex surgical process that requires intricate three-dimensional (3D) concepts for optimal functional and aesthetic outcomes. Conventional reconstruction of structural facial anomalies, such as those including cartilage or bony defects, typically rely on hand-carving autologous constructs harvested from a separate donor site, and shaping that cartilage or bone into a new structural framework. Tissue engineering has emerged in recent decades as a potential approach to mitigate the need for donor site morbidity while improving precision in the design of reconstructive construct. Computer-aided design and computer-aided manufacturing have allowed for a digital 3D workflow to digitally execute the planned reconstruction in virtual space. 3D printing and other manufacturing techniques can then be utilized to create custom-fabricated scaffolds and guides to improve the reconstructive efficiency. Tissue engineering can be paired with custom 3D-manufactured scaffolds to theoretically create an ideal framework for structural reconstruction. In the past decade, there have been several compelling preclinical studies demonstrating the capacity to induce chondrogenesis or osteogenesis in a custom scaffold. However, to date, these preclinical data have not yet translated into significant clinical experience. This translation has been hindered by a lack of consensus on the ideal materials and cellular progenitors to be utilized in these constructs and a lack of regulatory guidance and control to enable clinical application. In this review, we highlight the current state of tissue engineering in facial reconstruction and exciting potential for future applications as the field continues to advance.
Keywords: tissue engineering; 3D printing; scaffold; bioprinting